ChemInform Abstract: Novel Mixed Cobalt/Chromium Phosphate NaCoCr2(PO4)3 Showing Spin‐Flop Transition. Issue 41 (October 2015) - Souiwa, Khalifa; Chennabasappa, Madhu; Decourt, Rodolphe; Ben Amara, Mongi; Hidouri, Mourad; Toulemonde, Olivier
Abstract The new title compound is prepared by solid state reaction of a stoichiometric mixture of Na2CO3, Co(NO3)2, Cr(NO3)3, and (NH4)H2PO4 (Pt crucible, 1423 K, 48 h).